KINERJA PEGAWAI PADA BADAN PERENCANAAN PEMBANGUNAN DAERAH, PENELITIAN DAN PENGEMBANGAN KABUPATEN HULU SUNGAI UTARA - Hendrayani, Hendrayani; Hatriyani, Nia (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
The performance of employees of the Development Planning, Research and Development Agency of Hulu Sungai Utara Regency is good as a picture of quality human resources. The problem is that some employees are less thorough in carrying out their duties, lack of understanding about planning, and the problem of vacant positions, namely the Head of the Regional Development Planning, Control and Evaluation Division (P2EPD) and the lack of functional planner positions. The purpose of this study was to determine the performance of employees at the Development Planning, Research and Development Agency of Hulu Sungai Utara Regency and the factors that influence it. Descriptive qualitative research method, data collection techniques are interviews, observation and documentation. Data sources were taken through Convinence Sampling totaling 11 people. After the data is collected, it is reclassified and then analyzed to draw a conclusion, then test the reliability of the data, extend observation, increase persistence, and triangulation. The results of this study indicate that the performance of employees at the Development Planning, Research and Development Agency of Hulu Sungai Utara Regency is good. This can be seen in the indicators First, the Quality of Work from the skills and abilities of the average employee is quite good. Second, the quantity of employee tasks has not all been completed properly. Third, the timeliness of employees in completing work in accordance with the predetermined time. Fourth, the effectiveness of the use of resources is quite good, but it needs to be added to human resources and infrastructure that needs to be equipped. Fifth, independence and commitment have been carried out responsibly. The driving factors for employee performance at the Development Planning, Research and Development Agency of Hulu Sungai Utara Regency are mutual cooperation, good coordination, and the work environment. Factors that hinder Employee Performance at the Office of the Development Planning, Research and Development Agency of Hulu Sungai Utara Regency are lack of facilities and infrastructure and lack of employees. It is recommended that the Head of Bappelitbang should add human resources, give awards to employees who work professionally, provide opportunities for training to goods managers so that they carry out the right inventory and according to what is needed.